Infrared metrology using visible light - Paterova, Anna (2019)
Infrared (IR) spectroscopy and imaging are important tools in metrology, including material analysis, sensing and characterization. Although conventional methods of IR metrology are available, they face challenges related to the high cost and low efficiency of IR light sources and photodetectors. These challenges can be addressed by circumventing the need for IR-range components using tools and techniques of quantum optics.